2015
DOI: 10.1007/s13204-015-0419-5
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic oxidation of carbon monoxide over supported palladium nanoparticles

Abstract: Catalytic oxidation of CO with ozone had been studied over Al 2 O 3 and SiO 2 supported Pd nanoparticles which was synthesized by two different methods. The polyol method mainly resulted in highly dispersed Pd particles on the support, while the impregnation method resulted in agglomeration Pd particles on the support. Supported Pd nanoparticles synthesized from PdCl 2 in the presence of poly (N-vinylpyrrolidone) (PVP) by chemical reduction. The catalysts were characterized by X-ray diffraction, N 2 BET surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 53 publications
1
4
0
Order By: Relevance
“…The BET surface area values collected in Table 1 are consistent with those found in the literature for the different materials: Carbon Vulcan XC-72 [51,52], β-SiC [50], GF [53] and CNF LS [52]. Moreover, it can also be observed that the specific surface areas of the different catalysts were smaller than those of the initial support materials due to partial blocking of the support pores by Pt-Sn particles after metal precursor impregnation [54]. Pt-Sn catalysts supported on Carbon Vulcan XC-72 (for comparative purposes), CNF LS, CNF f-LS and TRGrO presented a combination of type I and IV isotherms (not shown here)…”
Section: Physicochemical Characterizationsupporting
confidence: 87%
“…The BET surface area values collected in Table 1 are consistent with those found in the literature for the different materials: Carbon Vulcan XC-72 [51,52], β-SiC [50], GF [53] and CNF LS [52]. Moreover, it can also be observed that the specific surface areas of the different catalysts were smaller than those of the initial support materials due to partial blocking of the support pores by Pt-Sn particles after metal precursor impregnation [54]. Pt-Sn catalysts supported on Carbon Vulcan XC-72 (for comparative purposes), CNF LS, CNF f-LS and TRGrO presented a combination of type I and IV isotherms (not shown here)…”
Section: Physicochemical Characterizationsupporting
confidence: 87%
“…BET surface area values are similar to those found in the literature for the materials C Vulcan, GF and CNF LS . On the other hand, after metal deposition, the specific surface area was smaller than that of the parent support materials, which could be attributed to partial blocking of the support pores by Pd nanoparticles . This effect is the opposite for the pore size and pore volume, which increase after adding Pd to the parent C Vulcan and CNF LS supports.…”
Section: Resultsmentioning
confidence: 99%
“…The light-off temperature follows the order of Pd/CeO 2 < Pd/TiO 2 < Pd/Al 2 O 3 < Pd/ZrO 2 ≤ Pd/ SiO 2 . The Pd/TiO 2 catalyst with lowest Pd dispersion has higher catalytic activity than Pd/Al 2 O 3 at lower temperatures which indicated that the Pd dispersion is not an important factor on supported Pd catalysts (Soni et al 2016;Sen et al 2016). The reduction of Pd ion to the metallic state is the most important factor controlling the CO oxidation.…”
Section: Chemisorptions Of Carbon Monoxide Over Palladium Oxide Catalmentioning
confidence: 99%